Severe Endobronchial Inflammation Induced by Aspiration of a Ferrous Sulfate Tablet - Lim, Sang Youn (Tuberc Respir Dis (Seoul), 2016)
Iron supplements such as ferrous sulfate tablets are usually used to treat iron-deficiency anemia in some elderly patients with primary neurologic disorders or decreased gag reflexes due to stroke, senile dementia, or parkinsonism. While the aspiration of ferrous sulfate is rarely reported, it is a potentially life-threatening condition that can lead to airway necrosis and bronchial stenosis. A detailed history and high suspicion of aspiration are required to avoid delays in diagnosis and treatment. The diagnosis can be confirmed by bronchoscopic examination and a tissue biopsy. Early removal of the aspirated tablet prevents acute complications, such as bronchial necrosis, hemoptysis, and lobar consolidation. Tablet removal is also necessary to prevent late bronchial stenosis. We presented the first case in Korea of a ferrous sulfate tablet aspiration that induced severe endobronchial inflammation.